Improving Mathematical Interest Among Muslim Primary School Students Via SITIC - Khairunneezam Mohd Noor; Nur Fazidah Asmuje@Asmuzi; Amirah Zainun; Nik Salida Suhaila Nik Saleh (Universiti Sains Islam Malaysia, 2024)
This article focused on the focal aim of analysing students’ perceptions in regards to their interest in Mathematics before and after they implement SITIC, a combination of Silat and mental arithmetic skills. A group of Muslim students (N=84) were selected from three primary schools in the district of Nilai, Negeri Sembilan on the basis of snowballing strategy. The students were exposed to 6 sessions of SITIC in a period of 2 weeks with the supervision of their teachers. A set of questionnaire was developed to look into the students’ interest towards mathematics before and after they join SITIC’s sessions. The findings shown that the interest of the respondents in their particular learning subjects increased after it was combined with interesting activities in SITIC. The findings were discussed together with the recommendations for future studies.